Boosting fermentable sugars by integrating magnesium oxide-treated corn stover and corn stover liquor without washing and detoxification. (September 2019) - Li, Jun; Liu, Dan; Zhang, Meng; Roozeboom, Kraig L.; Wang, Donghai
Highlights: Xylose in MgO-treated liquor was 42.6% of the total xylose in raw corn stover. Biomass liquor from MgO pretreatment was neutral without furfural and HMF formation. Treated biomass and liquor were hydrolyzed with no need for washing and detoxification. Integration of liquor and treated biomass increased xylose yield by 31.3%. Elimination of washing and detoxification largely simplifies the bioconversion process. Abstract: Integration of MgO-treated corn stover and corn stover liquor for enzymatic hydrolysis was studied to improve sugar yield and concentration as well as to simplify the bioconversion process. Results showed that under the same enzymatic hydrolysis conditions (2 mL enzyme/g biomass and 10% substrate loading), MgO-treated corn stover plus corn stover liquor had a similar glucose yield (70.4 vs. 68.8%) and concentration (40.4 vs. 41.5 g/L) but a higher xylose yield (56.6 vs. 25.3%) and concentration (16.7 vs. 10.6 g/L) compared with using MgO-treated corn stover only. Corn stover slurry from MgO pretreatment was near-neutral and free of 5-hydroxymethylfurfural and furfural, eliminating the need for washing and detoxification and lightening the burden for wastewater treatment. In addition, Tween 80 significantly reduced the irreversible binding of lignin to enzyme, increasing xylose and glucose yields by 14.7 and 6.2% and sugar concentration by 7.4 g/L, respectively.